Strategi Pengabdian Kepada Masyarakat dalam Pengembangan Lembaga Pendidikan yang Berkelanjutan di Kampus Ma’had Aisyah Bogor - Sonia, Gina; Lukman Hamid, Asep (Addabani: Interdisciplinary Journal of Islamic Education, 2023)
Mahad Aisyah is a special campus for Muslimah which has one study program namely women's/family Sharia Law. It has several community service activities such as training, literacy strengthening, community economic empowerment and workshops. The purpose of this research is to determine the performance of community service, the role of the surrounding community, especially in improving the quality of human resources, and strategies for developing sustainable education . This research uses a descriptive method with a qualitative approach. The research data was obtained from interviews with achievement indicators obtained from the guidelines of the Director General of Research and Technology and Higher Education and selected articles. The results of the research show that community service performance still needs to be developed. Mahad Aisyah is included in the category of Satisfactory Predicate. Community service activities are more on the religious and humanitarian side, as well as sustainable development as an international campus.